EFFECTS OF PRANAYAMA ON SELECTED PSYCHOLOGICAL VARIABLES AMONG INTER UNIVERSITY BADMINTON PLAYERS OF NASHIK ZONE - Varade, Mr. Suhas Shamrao (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The present study amid to check effect of Pranayama on selected psychological variables aggression and anxiety of inter university players due to the Pranayama: focus on breathing. To achieve the purpose of the study data was collected from 30 players. The age of the subjects were ranging from 18-21 years are considered as the total sample (N=30) of the study. The data collected was to conduct the anxiety and aggression tests on inter university badminton players of Nashik zone and treated with the statistical technique ‘t’ and found there is a significant improvement on selected psychological aspects of inter university Badminton players of Nashik zone.